Environmental changes and natural disasters - National Conference on'Environmental Pollution, Disaster Management, and Mitigation' (2006 : Parbhani, India); Babar, Md., 1966-; Dnyanopasak Shikshan Mandal's College of Arts, Commerce, and Science. Dept. of Geology (New Delhi : New India Publishing Agency, 2007)
Contributed papers presented at national conference on'Environmental pollution, disaster management and mitigation' held during Sept. 15th-16th, 2006 at Dnyanopasak Shikshan Mandal's College of Arts, Commerce, and Science, Parbhani, Maharashtra; organized by the Dept. of Geology; with reference to India
Includes bibliographical references
Keywords: Pollution -- Congresses; Environmental protection -- Congresses; Natural disasters -- Congresses; Hazard mitigation -- Congresses; Climatic changes -- Congresses